Codelivery of adavosertib and olaparib by tumor-targeting nanoparticles for augmented efficacy and reduced toxicity. (February 2023) - Wang, Wei; Xiong, Yuxuan; Hu, Xingyuan; Lu, Funian; Qin, Tianyu; Zhang, Li; Guo, Ensong; Yang, Bin; Fu, Yu; Hu, Dianxing; Fan, JunPeng; Qin, Xu; et al.
Abstract: Ovarian cancer (OC) ranks first among gynecologic malignancies in terms of mortality. The benefits of poly (ADP-ribose) polymerase (PARP) inhibitors appear to be limited to OC with BRCA mutations. Concurrent administration of WEE1 inhibitors (eg, adavosertib (Ada)) and PARP inhibitors (eg, olaparib (Ola)) effectively suppress ovarian tumor growth regardless of BRCA mutation status, but is poorly tolerated. Henceforth, we aimed to seek a strategy to reduce the toxic effects of this combination by taking advantage of the mesoporous polydopamine (MPDA) nanoparticles with good biocompatibility and high drug loading capacity. In this work, we designed a tumor-targeting peptide TMTP1 modified MPDA-based nano-drug delivery system (TPNPs) for targeted co-delivery of Ada and Ola to treat OC. Ada and Ola could be effectively loaded into MPDA nanoplatform and showed tumor microenvironment triggered release behavior. The nanoparticles induced more apoptosis in OC cells, and significantly enhanced the synergy of combination therapy with Ada plus Ola in murine OC models. Moreover, the precise drug delivery of TPNPs towards tumor cells significantly diminished the toxic side effects caused by concurrent administration of Ada and Ola. Co-delivery of WEE1 inhibitors and PARP inhibitors via TPNPs represents a promising approach for the treatment of OC. Statement of significance: Combination therapy of WEE1 inhibitors (eg, Ada) with PARP inhibitors (eg, Ola) effectively suppress ovarian tumor growth regardless of BRCA mutation status. However, poor tolerability limits its clinical application. To address this issue, we construct a tumor-targeting nano-drug delivery system (TPNP) for co-delivery of Ada and Ola. The nanoparticles specifically target ovarian cancer and effectively enhance the antitumor effect while minimizing undesired toxic side effects. As the first nanomedicine co-loaded with a WEE1 inhibitor and a PARP inhibitor, TPNP-Ada-Ola may provide a promising and generally applicable therapeutic strategy for ovarian cancer patients. Graphical abstract: Image, graphical abstract